MORPHOLOGICAL CHANGES IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE IN ELDERLY WOMEN AND COMPARATIVE ANALYSIS - Mirzakhmеdova Nilufar Askarovna. (Western European Studies, 2025)
Chronic obstructive pulmonary disease (COPD) is a heterogeneous lung condition characterized by chronic respiratory symptoms (dyspnea, cough, sputum production) and exacerbations due to airway (bronchitis, bronchiolitis) and/or alveolar (emphysema) damage, which cause persistent, often progressive airflow limitation. Exacerbations and comorbid conditions are an integral part of the disease and contribute significantly to the clinical picture. To assess the risk of COPD exacerbations, it is necessary to consider the patient's history of exacerbation frequency, including those requiring hospitalization within the last 12 months. If a patient has had even one exacerbation leading to hospitalization in the previous year (i.e., a severe exacerbation), they should be classified as high risk
Keywords: COPD; alveoli; microscopic; bronchioles